1934
DOI: 10.1017/s002185960000664x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium nitrate on the growth and nitrogen content of a lucerne and grass mixture

Abstract: IX. Summary and Abstract1. Inoculated lucerne was grown alone and in association with Italian rye grass, in pots of sand watered with food solution and given three different doses of sodium nitrate.2. The dose of nitrate did not affect the dry weight or nitrogen content of lucerne when grown alone, save that the highest dose checked the root growth somewhat.3. When lucerne and Italian rye grass were grown in association, the growth of the grass varied directly with the dose of nitrate applied, and the growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

1935
1935
1962
1962

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
2
8
1
Order By: Relevance
“…A seasonal variation in large-nodule number was observed, in agreement with other work (13,23) and a seasonal fluctuation in nitrogen fixation was also indicated by pigmentation observations. In 1956, nitrogen fixation probably reached a peak in June and July, after which it declined rapidly during August and September owing to the degeneration of leghaemoglobin to the green inactive form.…”
Section: Chemical Analysissupporting
confidence: 92%
“…A seasonal variation in large-nodule number was observed, in agreement with other work (13,23) and a seasonal fluctuation in nitrogen fixation was also indicated by pigmentation observations. In 1956, nitrogen fixation probably reached a peak in June and July, after which it declined rapidly during August and September owing to the degeneration of leghaemoglobin to the green inactive form.…”
Section: Chemical Analysissupporting
confidence: 92%
“…This result corroborates fully our previous findings (Virtanen and v. Hausen, 1931). Thornton and Nicol (1934) came to a similar conclusion in the related case of the uptake by grass of nitrogen made available by lucerne.…”
Section: Methodssupporting
confidence: 66%
“…Nobbe and Hiltner (1893) came to the conclusion that in water cultures the function of the nodules of leguminous plants is inhibited and that they do not supply their host with nitrogenous food when all nodules are submerged. According to Thornton (1930), the lack of air supply may inhibit nitrogen fixation by bacteria in the leguminous nodule. In agar cultures he found the most efficient nodules at the surface or at the points where the agar had cracked but no nitrogen fixation where all the nodules were deeply embedded in the agar.…”
mentioning
confidence: 99%
“…Botanical analysis of the mixtures indicates that this increase in yield was due mainly to increased productivity of the grass (Table 3). THORNTON and NICHOL (3) found that when lucerne and Italian ryegrass were grown in association the growth of the lucerne varied inversely with the dose of sodium nitrate. In the experiment reported here nitrogen stimulated growth in lucerne during the iirst year of application, but the increased yields over the control plots were not significant ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In AMERICA (1) it has been noted that nitrogen is of considerable value in establishing a new seeding of lucerne, but when lucerne was top dressed with nitrogen the effect was not marked, although increases in yield were noted. Working with sand cultures, THORNTON and NICHOL (3) found that doses of sodium nitrate did not affect the dry weight or nitrogen content of lucerne, when the lucerne was grown alone, save that high concentrations checked root growth somewhat.…”
Section: The Grassland Research Institute Hurley Berksmentioning
confidence: 99%